M cell targeting engineered biomaterials for effective vaccination. (February 2019) - Islam, Mohammad Ariful; Firdous, Jannatul; Badruddoza, Abu Zayed Md; Reesor, Emma; Azad, Mohammad; Hasan, Anwarul; Lim, Michael; Cao, Wuji; Guillemette, Simon; Cho, Chong Su
Abstract: Vaccines are one of the greatest medical interventions of all time and have been successful in controlling and eliminating a myriad of diseases over the past two centuries. Among several vaccination strategies, mucosal vaccines have wide clinical applications and attract considerable interest in research, showing potential as innovative and novel therapeutics. In mucosal vaccination, targeting (microfold) M cells is a frontline prerequisite for inducing effective antigen-specific immunostimulatory effects. In this review, we primarily focus on materials engineered for use as vaccine delivery platforms to target M cells. We also describe potential M cell targeting areas, methods to overcome current challenges and limitations of the field. Furthermore, we present the potential of biomaterials engineering as well as various natural and synthetic delivery technologies to overcome the challenges of M cell targeting, all of which are absent in current literature. Finally, we briefly discuss manufacturing and regulatory processes to bring a robust perspective on the feasibility and potential of this next-generation vaccine technology.